SIFAT MEKANIS GELAGAR KOTAK PERCOBAAN UNTUK KAYU KONSTRUKSI - Marolop Sinaga; Sadan Widarmana; Surjone Surjokusumo; A A Mattjik (Pusat Penelitian dan Pengembangan Hasil Hutan, 1989)
Experimental laminated box beam were constructed for their mechanical properties test. The pile component of box beam was prepared consisting of solid wood as upperside and downside flange and plywood or particleboard as left and right web. The dimension of box beam is 9.1 cm x 20 cm x 244 cm where the dimension of solid wood are 5.5 cm x3.5 cm x 244 cm and the dimensions of plywood and particleboard are 1.8 cm x 20 cm x 244 cm. All components were onnected by glue, nail and combination of both. The strength of box beam is based on the static bending test especially its modulus of elasticity (MOE) and modulus of rupture (MOR) by Baldwin universal testing machine with ASTM method.The results show that the experimental box beam produced had adequate MOE and MOR for construction purpose. The nail and nail-glue combination to connect plywood and particleboard components with solid wood give high value of MOE and MOR of box beam.